Native and alien grassland diversity respond differently to environmental and anthropogenic drivers across spatial scales - Bergamin, Rodrigo Scarton (2022)
Abstract Aims: To identify environmental and anthropogenic drivers of alpha-and beta-diversity for native and alien plant species. Location: Río de la Plata grasslands, South America (Argentina, Brazil and Uruguay; 27.3–39.1° S, 50.1–66.5° W). Methods: We assembled a data set of 597 vegetation plots distributed across the Río de la Plata grasslands. To assess the drivers of native and alien alpha-diversity (species richness), we performed a generalized least-squares regression using environmental and anthropogenic predictors. We evaluated differences in beta-diversity using Simpson's pairwise dissimilarity between pairs of plots and used multiple regression on distance matrixes to investigate environmental and anthropogenic drivers on compositional dissimilarity for both native and alien plant species. Results: Native species richness was higher in sites with less demanding environmental conditions, such as lower precipitation seasonality and soils with higher cation exchange capacity. Numbers of alien species were positively related to soil pH, cropland density and road density and negatively to precipitation seasonality, mean temperatures and soil cation exchange capacity. The compositional dissimilarity was similar for native and alien species assemblages (mean ± SD: 0.64 ± 0.16 and 0.64 ± 0.35 respectively). Areas having similar climates and being geographically close shared more taxonomically similar assemblages, for both native and alien assemblages, while soil had disparate effects. Compositional dissimilarity of alien plants decreased with increasing road density. Conclusions: Our results highlight a grassland ecosystem where native species richness is still shaped only by environmental factors, but both sets of factors influence its composition. On the other hand, alien plants carry a strong signal of both environmental and human factors. As time progresses the number of alien species tend to increase, eroding the patterns of native biodiversity. To avoid this, efforts should be made to reduce road encroachment and the conversion of natural grasslands into croplands.